Variations in epiphyseal fusion and persistence of the epiphyseal line in the appendicular skeleton of two identified modern (19th–20th c.) adult Portuguese and Italian samples. Issue 3 (19th April 2019) - Belcastro, Maria Giovanna; Pietrobelli, Annalisa; Rastelli, Elisa; Iannuzzi, Vincenzo; Toselli, Stefania; Mariotti, Valentina
Abstract: Objectives: The aim of this work is to study age, sex, and population variations in epiphyseal fusion and persistence of the epiphyseal line in the appendicular skeleton of two identified modern (19th–20th c.) adult skeletal samples, using a specifically designed macroscopic scoring method. The use of epiphyseal closure and persistence of the epiphyseal line as an adult‐age marker is also discussed. Materials and methods: This study examined 981 adult skeletons of both sexes from two identified modern (20th c.) skeletal samples from the Sassari Collection (Museum of Anthropology, University of Bologna, Italy) and the Colecção de Esqueletos Identificados (Museum of Anthropology, University of Coimbra, Portugal). Our scoring method considers a five‐degree scale, from nonfusion (Degree 0) to complete fusion (Degree 4). In addition, the persistence of the epiphyseal line, a feature that is not commonly collected during routine anthropological analyses, is taken into account here as Degree 3. Results: Intra‐ and interobserver errors of 1.2% and 5.2%, respectively, were found, suggesting a good reproducibility of this scoring method. Some sites show variable degrees of epiphyseal fusion still in adult skeletons (e.g., secondary center of ossification of the clavicle, iliac crest, ischial tuberosity, distal epiphysis of the radius and ulna). Conclusions: Population differences have been observed, showing a delay in the complete epiphyseal closure for the Sassari sample compared to the Coimbra sample. Degree 3 seems to be a good adult‐age indicator for individuals less than 35‐year‐old.